2017
DOI: 10.1155/2017/5631532
|View full text |Cite
|
Sign up to set email alerts
|

Quality, Microstructure, and Technological Properties ofSheepMeat Marinated in Three Different Ways

Abstract: The objective of this study was to explore the effect of 24 and 48 h alkaline (2% pentasodium tripolyphosphate), acid (2% sodium lactate), and water-oil marinating (water : sun flavor oil = 1 : 1 and 2% salt) as well as brine soaking (2% salt) on microstructure, changes in protein, and lipid fractions and technological properties of sheep (m. Longissimus dorsi). Strong myofibrillar fragmentation after 48 h alkaline marinating was observed. Significant swelling and increasing of spaces between myofibrils were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(40 reference statements)
0
10
0
1
Order By: Relevance
“…This could be justified by the decrease of pH during marination, which improves the meat water-holding capacity [ 8 , 37 ]. Furthermore, a main role in improving the water-holding capacity of beef meat is of citric acid, a food acidulant [ 60 ] which was identified in all analysed samples. Marinades are responsible also for the reducing water loss during cooking owing to the developing of an extra succulent texture on the meat surface [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could be justified by the decrease of pH during marination, which improves the meat water-holding capacity [ 8 , 37 ]. Furthermore, a main role in improving the water-holding capacity of beef meat is of citric acid, a food acidulant [ 60 ] which was identified in all analysed samples. Marinades are responsible also for the reducing water loss during cooking owing to the developing of an extra succulent texture on the meat surface [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lamb fat has a high concentration of vitamin E, but low stearin. Among all the types of meat, lamb has an optimum balance between polyunsaturated fatty acids ω6/ω3, which is equal to 2.5:1 and positively affect human health (lower blood pressure, protect against irregular heartbeats, and lower your risk for heart diseases) [23]. The highest ash content is determined in turkey meat (2.37% in red and 1.65% in white meat), in goat meat -1.45% and in maral meat and lamb is less than 1%.…”
Section: Resultsmentioning
confidence: 99%
“…By the high content of fluorine (twice higher than in beef), consumption of lamb promotes the hardness of enamel, and prevents carbohydrate metabolism disorder in diabetes. One of the main advantages of lamb is its hypoallergenicity [10]. Goat meat's nutritive value is comparable with lamb, but less fatty, and has a pleasant flavor, more tender, and moist.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that sodium lactate marinating at 2% improved the water-holding capacity, solubility of the protein fraction, and marinade uptake of sheep meat [78].…”
Section: Sheep Meat Decontamination Of Sheep Carcasses Bymentioning
confidence: 99%